Ring finger protein 180 inhibition lymphatic metastasis of gastric cancer - Jing-Yu Deng (临床与病理杂志, 2026)
Objective: To explore the potential mechanisms of lymphatic metastasis of GC cells regulated by ring finger protein (RNF180). Methods: Associations between clinicopathologic, survival data, and RNF180 expression in GC tissues were analyzed. The effects of RNF180 reexpression and genome microarraywere determined in growth, proliferation, invasion, and lymphangiogenesis assays. Results: RNF180 was silenced or down-regulated in 76.1%of GC tissues compared with 41.8% of paired nontumor tissues. RNF180 protein expression in GC tissues was negatively related to the number of metastatic lymph nodes. RNF180 was down-regulated in 100% (7 of 7) of GC cell lines. Re-expression of RNF180 in HGC-27 GC cells reduced colony formation, proliferation, migration and invasion in vitro, and tumor growth and tumor lymphangiogenesis in mice it also down-regulated HGF, MMP-2, MMP-14, VEGF-C/D and CCR-7 in vitro, and Podoplanin in tumor tissue of mice. Conclusion: RNF180 is a suppressor gene involved inthe several biological events of GC cell including the proliferation, invasion, and tumor lymphangiogenesis.